Kim Namjoon’s Speech at the 2018 United Nations General Assembly: The Intentions and Impacts - Ayu Indyra Cahayarani (Institute of Research and Community Outreach - Petra Christian University, 2023)
This study, using a qualitative approach, was conducted to find out the types of illocutionary acts in the speech of Kim Namjoon at the 2018 United Nations General Assembly, including the intentions and the impacts. The speech on “Generation Unlimited”, was aimed to help young people all over the world to help end bullying and violence by sharing kind notes. In conducting the research, the writer used the theory proposed by George Yule (1996) completed by the related theory by O’Keeffe, Clancy, and Adolphs (2011). The findings reveal various intentions through the illocutionary acts and the impacts through the written responses as the perlocution. The intentions through the representative acts were to inform people about his struggles in the past. The intentions through the directive acts were to get the audience to begin speaking up and expressing what they believed. The impact of this speech was that it touched the audience's hearts; they got inspired by the speech to never give up, and they would now continue to love and speak for themselves even if it was hard. In conclusion, Kim Namjoon’s speech at the 2018 United Nations General Assembly resulted in inspiring and motivating impacts on the audience viewed from their written responses.